Topical issues of stimulating the work of civil servants (Law and Safety, 2021)
Emphasis is placed on the fact that one of the topical and urgent issues of reforming the system of public administration in Ukraine in general and the institution of civil service in particular is to improve the mechanism of stimulating the work of civil servants. It is noted that the approach chosen by the official authorities to improve the effectiveness of incentives for civil servants is limited mainly to the revision of approaches to their remuneration. At the same time, such important elements of the mechanism of stimulating employment, such as guaranteed career growth, protection from administrative pressure and illegal disciplinary action, guaranteed application of incentives and rational organization of the work process, do not receive due attention and development. It is emphasized that one of the problems of improving the incentives for civil servants is the lack of a clear understanding of the nature and objectives of incentives, its relationship with such phenomena as motivation and encouragement of employees.Scientific views on the understanding of the essence and content of work incentives, as well as its relationship with such related phenomena as motivation and encouragement are considered. Attention is paid to the conceptual and legislative principles of stimulating the work of civil servants. The problematic aspects of the legislative regulation of stimulating the work of civil servants are identified, as well as the important conditions, the implementation of which is necessary to ensure effective stimulation of the work of civil servants, are outlined. Attention is paid to the role of professional growth and guaranteed career advancement as important elements of stimulating employment. It is emphasized that the requirements of legality and professional ethics cannot be violated for reasons of ensuring high efficiency and effectiveness of civil servants. Particular attention is paid to strengthening legislative guarantees for incentives for civil servants who have made a significant personal contribution to the activities of the state bodies where they work, to reforming and developing the public administration system in general and the civil service in particular.
Keywords: public administration; civil servant; stimulation of service and labor activity; motivation of employees; encouragement of civil servants.